The Quest for a Better Life in a Better World: The Role of Adult Education in Advancing Inclusion of SMGV Learners and Citizens - Andre P. Grace (Adult Education Research Conference, 2011)
This paper investigates the space of SMGV (sexual minority and gender variant) learners in lifelong learning and constituent adult education from transnational perspectives. It discusses the ongoing fiction of adult education as globally inclusive social education. It highlights the construction of a limited social as adult education is taken up in exclusionary contexts where interest groups frequently marginalize sexual orientation and gender identity as power relationships.
Keywords: sexual minority and gender variant; transnational homophobia; queer critical pedagogy